Effect of urban changes on carbon monoxide spatial variation using LST and urban indices of Landsat 8 OLI / Rabiatul Najwa Bahrin - Bahrin, Rabiatul Najwa (2022)
Carbon Monoxide (CO) is one of the major threats to communities' health and the environment. In relation to spatial features affecting the increasing CO over cities, it is crucial to understand CO spatial variation concentration due to the built-up areas, vegetation, and temperature. This research aims to determine the effect of urbanization on the spatial variation of Carbon Monoxide (CO) for the years 2014, 2016, 2018 and 2020 in Selangor using annual Air Pollution Index (API) and Landsat 8 OLI/TIRS satellite-derived of Land Surface Temperature (LST) and Urban Indices. In this study, the spatial statistical approach of Multi Geographically Weighted Regression (MGWR) was used to determine the spatial variation of air pollutants in the Selangor area based on the relationships between CO with LST, Normalized Difference Vegetation Index (NDVI), Normalized Difference Built-Up Index (NDBI) and Urban Index (UI). The results from MGWR have shown that there were strong and significant correlations in 2014 (R2 = 0.989) while 2016, 2018 and 2020 (R2 = 0.992) in the relationships between CO and the urban parameters. The finding indicates the local spatial variations of CO concentrations due to the NDVI, NDBI, UI and LST where the areas with low vegetation, dense urbanization, and high LST are consistently associated with increased concentrations of CO. This outcome will aid urban and environmental planners in developing urban planning policies and making Selangor more resilient to the effects of air pollution.